Worldcom and Vivendi reeling from communications crash.
Within a few days, turmoil engulfed two giants of telecommunications and media: Paris-based Vivendi Universal SA and Clinton, Miss-based WorldCom Inc. Each, in its own way, fell victim to the failure of the communications sector to keep growing at the breakneck speeds still expected two years ago. Ironically, there is nothing wrong with either WorldCom or Vivendi that debt (and hype) reduction-inside or outside of bankruptcy proceedings-won't solve. Unlike so many of the dot-coms, both companies have real, cash-generating businesses, and both have assets to put on the block. But both also need time to sort out their affairs, and await an economic environment less obsessed with scandal and more open to the still-real possibilities of-an unpopular word these days-convergence. With the communications collapse and the failure of the broadband vision to materialize as scheduled, each company was left with crushing overhangs of debt. News of accounting irregularities, compounded at WorldCom by personal transgressions of executives, made things much worse.
Keywords: Vivendi; Worldcom; Accounting irregularities; Cash-generating businesses; Communications crash; Debt reduction; Economic environment